Chemical profiling and discrimination of green tea and Pu-erh raw tea based on UPLC–Q–Orbitrap–MS/MS and chemometrics. (1st October 2020) - Zhong, Jiayi; Chen, Ning; Huang, Sichen; Fan, Xiaowei; Zhang, Yi; Ren, Dabing; Yi, Lunzhao
Highlights: Chemical profiles of Pu-erh raw tea and traditional green tea were revealed. 145 components were annotated by three-level qualitative strategy. The integrated filtering strategy was employed to eliminate the interference mass spectra. 23 characteristic components were screened by PLS-DA and VIP method. Abstract: To reveal the characteristic chemical profiles of Pu-erh raw tea (PRT) and traditional green tea (TGT), a high-throughput analytical method based on UPLC-Q-Orbitrap-MS/MS was proposed. 145 components were characterized with a three-level qualitative strategy and the integrated filtering strategy combining nitrogen rule, mass defect, and diagnostic ions information. 124 components were quantified using an internal standard method. The total contents of flavan-3-ols and derivatives, phenolic acids and derivatives were higher in PRT than TGT, while flavonoids were reversed. Furthermore, partial least squares–discriminant analysis (PLS-DA) models were established to classify TGT and PRT. 23 characteristic components were revealed by variable importance in projection method. Their difference in content is between 1.5 and 7.3 times for PRT and TGT. The results showed the chemical characteristics of TGT and PRT clearly and comprehensively. The high-throughput method demonstrated considerable potential in the analysis of complex chemical system, such as food and herbs.